Pengaruh Harga, Keragaman Barang dan Kualitas Pelayanan terhadap Keputusan Pembelian (Studi pada Konsumen Swalayan Aneka Jaya Ngaliyan Semarang) - Tendy Yedida C; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
One of many proof that tradig market in Indonesia growing is increasing of total supermarket. Retail Company required to fullfilling consume desire. Aneka Jay Supermarket in Ngaliyan is a supermarket in semarang which still growing comparing its competitor with same field.This study aims to determine the effect of price, product variation, and service quality towards purchasing decision in Swalayan Aneka Jaya Ngaliyan. Population in this study are consumen from Swalayan Aneka Jaya in Ngaliyan and taking sample consist 95 respondence. The data were analyzed through correlation coefficient, determination coefficient, simple linear regression, and t test.Based on the survey results revealed that price, product variation and service quality have significant effect on purchasing decision., either partially or simultaneously. Independent variables that have the biggest influence on purchasing decisions was the variable of product variation.In conclusion, obtained the three variables, that is price, product variation, and service quality have dominant effect with purchasing decision whereas product variation have the biggest effect from those three variables. Suggestion from author is increase promotion activity that have relation with price, gave discount of certain moment, increase the product variation, facility of supermarket, and increase service quality from worker to make cosumen felling impulse purchasing and repeat purchasing.